Elucidating Structure Property of Polyethylene/CNT Nanocomposite by in situ SFM Deformation Tests - Adhikari, Rameshwor; Godehardt, Reinhold; Lebek, Werner; Michler, Goerg H.; Potschke, Petra (Journal of Nepal Chemical Society, 2010)
Deformation behavior of nanocomposites based on an ethylene/1-octene copolymer and multiwalled carbon nanotube (CNT) was investigated by means of an atomic force microscope (AFM). Via a special tensile module integrated to an optical microscope, it was possible to record the stress-strain diagrams of the composites using miniaturized tensile specimens. By analyzing strain induced structural changes occurring at different successively applied loads, it was possible to correlate the deformation mechanisms occurring on various length scales (i.e. at macroscopic, microscopic as well as nanoscopic levels) to different degrees of deformation. It was noteworthy that, contrasting the properties of other nanocomposites described so far in the literature, both the strength and toughness of the composites were found to enhance. It was found that the deformation of the composite on nanoscopic scale was inhomogeneous owing to anisotropic properties of the CNTs and their alignments. After unloading the sample, the nanostructure of the original material was fully regenerated explaining the macroscopically observed elastomeric properties. Keywords: Ethylene/1-octene copolymer; CNT; Deformation mechanism; AFM; In situ deformation tests DOI: 10.3126/jncs.v26i0.3626 Journal of Nepal Chemical Society Vol. 26, 2010 Page: 22-30